ANALISIS PENGARUH PENGETAHUAN TENTANG SEKS TERHADAP PERILAKU SEKSUAL REMAJA DI INDONESIA MENGGUNAKAN REGRESI LOGISTIK MULTINOMIAL - Muhammad Ricky Pranata; Ray Sastri (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2020)
Sexual impulse will begin to appear in a person when entering adolescent age. The adolescent does different things to fulfill their sexual impulse such as holding hands, hugging, kissing, touching and even having sex. Because this is a new experience to them, they need a lot of information about sexuality such as the reproductive system, sexually transmitted diseases, and others. They can get it in school, the internet, or discuss it with others. The way they deal with their sexual impulse is largely determined by their individual characteristics, knowledge, and discussion partners. This study aims to determine the effect of individual characteristics, knowledge, and information sources on adolescent sexual behavior. This study uses data from the Indonesian Demographic and Health Survey (SDKI) in 2012 with a unit of analysis adolescence age of 15â”€19 years and is never married. The method of analysis uses multinomial logistic regression with adolescent sexual behavior as response variables divided into three categories; quiet (ignore it), minor sexual activity, and serious (touching the sensitive area and or having sex). The conclusion is the individual's background, sexual knowledge, and sources of information influence sexual behavior both in boy and girl. Serious sexual behavior tends to occur in adolescents who do not attend school, a man who understands about contraception, girls who misunderstand about pregnancy, and those who discuss sexuality with friends.